Implementasi Program Kota Tanpa Kumuh (KOTAKU) di Desa Harjosari Kidul Kecamatan Adiwerna Kabupaten Tegal Tahun 2017 – 2019 - Erny Rosyanti; Akhmad Habibullah; Awalia Retnowati (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
Population growth in Indonesia which is increasing every year causes the land to become denser and affects the quality of settlements. Based on Presidential Regulation Number 2 of 2015 concerning the 2015-2019 National Medium-Term Development Plan, it provides a mandate in the scope of settlement development in urban areas through the settlement of quality settlements. The government through the Directorate General of Human Settlements runs the City Without Slums Program (KOTAKU). The KOTAKU program aims to support the realization of livable, productive, and sustainable urban settlements. With “Movement 100-0-100”. The problem in this research is that in the implementation of the KOTAKU program in Harjosari Kidul Village, there is still one resident who is less willing to be a participant related to the use of his personal land and limited funds to handle the location so the location is still not handled properly. This study seeks to examine the implementation of the City Without Slums (KOTAKU) program in Harjosari Kidul Village, as well as to examine what obstacles are in the implementation of the program. The research method used is a descriptive qualitative approach. The research wants to examine how it is implemented by using the theory of implementation from expert George C Edwards III. The results of this study that the Implementation of the City Without Slums (KOTAKU) Program in Harjosari Kidul Village is already exemplary, based on the problems of residents who were initially unwilling to become participants due to their private land, now the residents are willing but are still having problems handling the location due to limitations. funds to handle the location so that it still leaves slums in the location.